2015
DOI: 10.3945/jn.115.210716
|View full text |Cite
|
Sign up to set email alerts
|

Cheddar Cheese Ripening Affects Plasma Nonesterified Fatty Acid and Serum Insulin Concentrations in Growing Pigs

Abstract: Intake of long-term ripened cheddar improved indicators of insulin sensitivity in growing pigs compared with short-term ripened cheddar. This may also be important for human health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…An exception was the intake of cheese which may have different effects on the risk of type 2 diabetes according to, for example, fat content and ripening. Longer ripening time of cheddar cheese has been shown to reduce the amount of plasma non-esterified fatty acids and serum insulin compared with cheese with a shorter ripening time in a pig model ( 21 ) . Intake in some of the dairy product subgroups was low, especially that of whole-fat milk, low-fat yogurt products, whole-fat yogurt products and buttermilk.…”
Section: Discussionmentioning
confidence: 99%
“…An exception was the intake of cheese which may have different effects on the risk of type 2 diabetes according to, for example, fat content and ripening. Longer ripening time of cheddar cheese has been shown to reduce the amount of plasma non-esterified fatty acids and serum insulin compared with cheese with a shorter ripening time in a pig model ( 21 ) . Intake in some of the dairy product subgroups was low, especially that of whole-fat milk, low-fat yogurt products, whole-fat yogurt products and buttermilk.…”
Section: Discussionmentioning
confidence: 99%
“…There are however a number of issues which reduce the ability to draw clear conclusions in relation to cheese and CVD risk. For example it is not known what the effects would be of the many individual cheese types which differ in macronutrient content, extent of fermentation, and food matrix/structure and a recent study has shown that the length of the cheese ripening period can influence insulin sensitivity, at least in a pig model .…”
Section: Saturated Fatty Acidsmentioning
confidence: 99%
“…In addition to the specific dairy proteins, different dairy foods have been shown to have a range of lipid effects (62) . It has been reported that cheese may have a differential effect on blood lipids compared with other dairy foods (34,63,64) , with prolonged ripening of cheddar cheese resulting in more pronounced lipid-lowering effects in a pig model (65) . A meta-analysis that included five of these RCT showed that when compared with butter intake, cheese consumption reduced LDL-C by 6·5 % (−0·22 mM/l; 95 % CI −0·2, −0·14) and HDL-C by 3·9 % (−0·05 mM/l 95 % CI −0·09, −0·02) but had no effect on TAG (66) .…”
Section: Differential Impact Of High-and Low-fat Dairy Foodsmentioning
confidence: 99%